Penentuan Alternatif Startegi Pemasaran pada CV Citra Hasil Hutan Mandiri di Kabupaten Kubu Raya - Lim, Andry Lindi (MABIS, 2011)
Consumers determine the sales and profits of a firm by their purchasing decisions. As such, their motives and actions determine the economic viability of the firm. In the past, many business firms were not overly concerned with consumers did what they did. Today, however, business managers are more likely to realize that they must gain an understanding of consumers if their marketing strategies are to be successful. This awareness has created a new and more efficient focus in developing marketing strategies. Success of a firm is mostly determined by strategic used to determine type of business, like what goal to reach and how to maintain resources from a firm itself. In reaching the goal, the strategic marketing has a similar quite important function. Marketing function sometimes assumed as a pier key to goal itself, because according to marketing theory said goal of a firm relies on adaptability of the firm itself to analysis changing complex and full of activity changes.The goal is to get maximal sales volume and strategy used to face environmental changes. Descriptive analysis used, interviewing head of firm and study of documentary, and qualitative analysis technique. It is concluded that firm uses growth specific strategy and operating level.The firm is urged to extend market wider consequently